(untitled) (Journal of International Studies, 2022)
Goods and Services Tax or GST is one of the most controversial taxes, causing dissatisfaction among the people. The distribution of justice and the implementation and effectiveness of GST policies tend to be the most frequently debated issues. The objective of this study is to examine the implementation, impacts, effectiveness, and challenges of GST policy in Southeast Asian countries, particularly Malaysia and Singapore. By employing a critical analysis perspective such as from Marxism’s lens of view, it is expected that this article will provide a new perspective in analysing GST policy implementation in the region. A descriptive qualitative analysis approach was used in this study, emphasising the content analysis method and the data obtained from official sources and literature studies. The study found that GST contributed to Singapore and Malaysia’s economy and revenue. Nevertheless, the GST impact affected the citizens of Singapore and Malaysia, especially the lower-income earners. The study argued that there is a dilemma in the GST tax policy implementation. It can be assumed through the findings that the GST policy did not meet the conscience of the Marxist perspective as it is regressive. Thus, in several parts of GST implementation, it has both advantages to the country’s production and productivity. On the other hand, it disadvantages society, particularly the lower- and middle-class groups.